Improved impact resistant capacity of segmental column with fibre reinforced polymer wrap - Zhang, Xihong; Hao, Hong (Elsevier, 2019)
Our previous studies investigated the response of precast segmental columns subjected to lateral impact loading, and found that the columns exhibited better flexibility and impact resistance capability as compared to monolithic cast-in-place column. The damage and failure of segmental column were mainly due to flexural compression induced damages when subjected to mid-span impact, and concrete shear failure when subjected to near base impact. In this paper, we utilize FRP to wrap the concrete segments to improve its impact resistant capacity. Laboratory impact tests on scaled columns are conducted. The columns are impacted at mid-span, segmental joint near column base and directly onto the centre of the bottom concrete segment, for which the column responses are respectively associated primarily with the flexural bending mode, combined bending and shear mode, and direct shear deformation mode. The responses of the columns are examined and compared with those non-retrofitted columns. Then, a detailed three-dimensional numerical model of the segmental column is generated and validated with lab test results. The numerical model can be used to calculate the responses of the segmental columns subjected to lateral impact loading for design analyses.